Regulation of Long Non-coding RNAs and MicroRNAs in Heart Disease: Insight Into Mechanisms and Therapeutic Approaches - Collins, Lucy; Binder, Pablo; Chen, Hongshan; Wang, Xin (Frontiers in Physiology, 2020)
Cardiovascular disease is the leading cause of mortality worldwide and there is an increasing need to identify new therapeutic targets that could be used to prevent or treat these diseases. Due to recent scientific advances, non-coding RNAs are widely accepted as important regulators of cellular processes, and the identification of an axis of interaction between long non-coding RNAs (lncRNAs) and micro RNAs (miRNAs) has provided another platform through which cardiovascular disease could be targeted therapeutically. Increasing evidence has detailed the importance of these non-coding RNAs, both individually and in an axis of regulation, in the processes and diseases involving the heart. However, further investigation into the consequences of targeting this mechanism, as well as refinement of how the system is targeted, are required before a treatment can be provided in clinic. This novel level of genomic regulation provides an exciting potential novel therapeutic strategy for the treatment of cardiovascular disease.